Responsible public communication in violent contexts: The case of Zacatecas, Mexico - Flores Pérez, Claudia Cecilia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Through this article, an analysis is made of the public communication of the government of Zacatecas, Mexico, trying to identify its degree of responsibility towards the citizenry, by virtue of the violent context in which it has been living for more than a decade, placing it as one of the most violent entities in the country. Likewise, in a comparative manner, the collective efforts of an organized digital citizenry are analyzed, which, faced with the lack of communication from the government, have created their own means to keep an expectant and fearful society informed of the criminal acts that have been normalized, with the sole purpose of protect their integrity and their life, in the face of a common suffering: violence and insecurity.